2009
DOI: 10.14723/tmrsj.34.67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gases on Pyroelectric Properties of PVDF/TiO<sub>2</sub> Treated by Plasma Etcher

Abstract: Composite thin films containing PVDF and TiO 2 have been prepared by using spin coating technique. The highest pyroelectric activity as measured by quasi static method is shown by the composite thin films containing 20 wt% of TiO 2 . The doping of TiO 2 in PVDF thin films has reduced the optimum poling electric field needed to be applied in order to observe pyroelectric activity in the composite thin films. Plasma treated composite thin films with Argon (Ar) gas has further increased the pyroelectric coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The pyroelectric coefficients of the series of poled composite thin films were determined by a quasi-static method. Details of the experimental setup are reported in our previous work [11]. The triangular heating and cooling cycle was set with ramping rates of 0.01-0.05°C/s (controlled by LakeShore 330 temperature controller) for an amplitude DT = 1°C at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The pyroelectric coefficients of the series of poled composite thin films were determined by a quasi-static method. Details of the experimental setup are reported in our previous work [11]. The triangular heating and cooling cycle was set with ramping rates of 0.01-0.05°C/s (controlled by LakeShore 330 temperature controller) for an amplitude DT = 1°C at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a homogeneous and thin film that is free from pin-holes can be spin-casted onto aluminized glass substrates. Previous work [26] has shown that the optimum dispersed concentration of TiO 2 in PVDF composites is in the range of 10-30 wt%. The pyroelectric activity of the composite thin films dispersed with the optimum amounts of TiO 2 has exhibited the highest pyroelectric activity.…”
Section: Methodsmentioning
confidence: 98%